Fronto-striatal circuits in response-inhibition: Relevance to addiction - Morein-Zamir, Sharon (Brain Res, 2015)
Disruptions to inhibitory control are believed to contribute to multiple aspects of drug abuse, from preexisting vulnerability in at-risk individuals, through escalation to dependence, to promotion of relapse in chronic users. Paradigms investigating the suppression of actions have been investigated in animal and human research on drug addiction. Rodent research has focused largely on impulsive behaviors, often gauged by premature responding, as a viable model highlighting the relevant role of dopamine and other neurotransmitters primarily in the striatum. Human research on action inhibition in stimulant dependence has highlighted impaired performance and largely prefrontal cortical abnormalities as part of a broader pattern of cognitive abnormalities. Animal and human research implicate inhibitory difficulties mediated by fronto-striatal circuitry both preceding and as a result of excessive stimulus use. In this regard, response-inhibition has proven a useful cognitive function to gauge the integrity of fronto-striatal systems and their role in contributing to impulsive and compulsive features of drug dependence. This article is part of a Special Issue entitled SI:Addiction circuits.